Breaking the “Hurt People Hurt People” Cycle: Examining The Influence of Family Dysfunction and Disorganized Attachment on Dating Violence - Nadhira Fairuzia Azzahwa; Pradipta Christy Pratiwi (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Dating violence remains a serious social and public health issue, often understood through the intergenerational perspective of the 'hurt people hurt people' cycle. This study examined the moderating role of disorganized attachment in the relationship between family dysfunction and dating violence among young adults. A quantitative cross-sectional survey design was employed with 141 participants aged 18-25 years who had been or were currently in romantic relationships for at least 6 months and came from dysfunctional family backgrounds. Data were collected online using three validated instruments: the Chinese Family Assessment Inventory (CFAI; α = 0.946), Adult Disorganized Attachment scale (ADA; α = 0.849), and Conflict in Adolescent Dating Relationships Inventory (CADRI; α = 0.956). Moderated Regression Analysis (MRA) with hierarchical regression was conducted using SPSS Statistics 27. Results indicated that while both family dysfunction (β = 0.149, p = 0.020) and disorganized attachment (β = 0.666, p < 0.001) significantly predicted dating violence, the moderating effect of disorganized attachment was not statistically significant (ΔR² = 0.012; F = 3.883; p = 0.051), though it approached conventional significance levels. The combined model explained 55.1% of the variance in dating violence. These findings suggest that dating violence is influenced by both family experiences and internal psychological mechanisms, with disorganized attachment emerging as a stronger proximal predictor. Prevention interventions should target not only family background but also attachment patterns and emotion regulation.Kekerasan dalam pacaran merupakan masalah sosial dan kesehatan masyarakat yang serius, sering dipahami melalui perspektif intergenerasi dalam siklus 'hurt people hurt people'. Penelitian ini mengkaji peran moderasi disorganized attachment pada hubungan antara disfungsi keluarga dan kekerasan dalam pacaran pada dewasa muda. Desain penelitian kuantitatif cross-sectional melibatkan 141 partisipan berusia 18-25 tahun yang pernah atau sedang menjalani hubungan romantis minimal 6 bulan dan berasal dari latar belakang keluarga disfungsional. Data dikumpulkan secara daring menggunakan tiga instrumen tervalidasi: Chinese Family Assessment Inventory (CFAI; α = 0,946), Adult Disorganized Attachment scale (ADA; α = 0,849), dan Conflict in Adolescent Dating Relationships Inventory (CADRI; α = 0,956). Moderated Regression Analysis (MRA) dengan regresi hierarkis dilakukan menggunakan SPSS Statistics 27. Hasil menunjukkan bahwa disfungsi keluarga (β = 0,149, p = 0,020) dan disorganized attachment (β = 0,666, p < 0,001) secara signifikan memprediksi kekerasan dalam pacaran, namun efek moderasi disorganized attachment tidak signifikan secara statistik (ΔR² = 0,012; F = 3,883; p = 0,051), meskipun mendekati batas signifikansi konvensional. Model gabungan menjelaskan 55,1% varians kekerasan dalam pacaran. Temuan ini menunjukkan bahwa kekerasan dalam pacaran dipengaruhi oleh pengalaman keluarga dan mekanisme psikologis internal, dengan disorganized attachment muncul sebagai prediktor proksimal yang lebih kuat. Intervensi pencegahan perlu menargetkan tidak hanya latar belakang keluarga tetapi juga pola kelekatan dan regulasi emosi.